Meiotic genes and sexual reproduction in the green algal class Trebouxiophyceae (Chlorophyta) - Fučíková, Karolina; Pažoutová, Marie; Rindi, Fabio (Journal of phycology, 2015)
Sexual reproduction is widespread in eukaryotes and is well documented in chlorophytan green algae. In this lineage, however, the Trebouxiophyceae represent a striking exception: in contrast to its relatives Chlorophyceae and Ulvophyceae this group appears to be mostly asexual, as fertilization has been rarely observed. Assessments of sexual reproduction in the Trebouxiophyceae have been based on microscopic observation of gametes fusing. New genomic data offer now the opportunity to check for the presence of meiotic genes, which represent an indirect evidence of a sexual life cycle. Using genomic and transcriptomic data for 12 taxa spanning the phylogenetic breadth of the class, we tried to clarify whether genuine asexuality or cryptic sexuality is the most likely case for the numerous putatively asexual trebouxiophytes. On the basis of these data and a bibliographic review, we conclude that the view of trebouxiophytes as primarily asexual is incorrect. In contrast to the limited number of reports of fertilization, meiotic genes were found in all genomes and transcriptomes examined, even in species presumed asexual. In the taxa examined the totality or majority of the genes were present, Helicosporidium and Auxenochlorella being the only partial exceptions (only four genes present). The evidence of sex provided by the meiotic genes is phylogenetically widespread in the class and indicates that sexual reproduction is not associated with any particular morphological or ecological trait. On the basis of the results, we expect that the existence of the meiotic genes will be documented in all trebouxiophycean genomes that will become available in the future.
Keywords: meiotic genes; Trebouxiophyceae; Chlorophyta; sexual reproduction; green algae; algal genomes